Composition and distribution of medically important phlebotomines (Diptera: Psychodidae) in the municipalities of Tierralta and Valencia (Córdoba, Colombia) (2017)
ABSTRACT: Background & objectives: Ecoepidemiological studies of cutaneous leishmaniasis and regular monitoring of Lutzomyia species have generated a knowledge base that can be used for control and prevention strategies targeted at the disease transmission dynamics in focal areas of Colombia. In this study, the presence and spatial distribution of phlebotomines of medical importance in the municipalities of Tierralta (El Loro and Tuis Tuis villages) and Valencia (Guadua and Mieles villages) were determined. Methods: Entomological surveys were performed in 2015 (months of June, September and November) and samples were collected via CDC-traps located in intradomicilary and peridomiciliary areas in the municipalities of Tierralta and Valencia (Department of Córdoba, Colombia). Active searches were also carried out with a mouth aspirator to collect adult phlebotomines from resting sites. ANOVA and Kruskal-Wallis tests were performed to assess if the differences between the communities of phlebotomines. Spatial distribution maps of the Lutzomyia species were generated. Results: A high species diversity of Lutzomyia was observed with a total of 1677 Lutzomyia individuals belonging to 12 species. Among these species, Lu. panamensis was the most abundant (80.18%). The composition of the intradomicilary and peridomiciliary phlebotomines varied significantly (F = 0.9962; df = 1; p = 0.02895). Species like Lu. carpenteri, Lu. camposi, Lu. dysponeta, Lu. atroclavata and Lu. yuilli yuilli were recorded for the first time in the Department of Córdoba, Colombia. Interpretation & conclusion: The spatial distribution shows that Lu. panamensis and Lu. gomezi are predominant and present in areas with high concentration of houses. This study provides basic information on new records of phlebotomines in the Department of Córdoba. The results suggest that greater vector-human contact occurs in the peridomiciliary environment and that a high number of Lutzomyia species associated with the transmission of leishmaniasis are present in Colombia.